Brotherhood of blades II [videorecording (DVD)] : the infernal battlefield - Lu, Yang (Film director); Zhang, Zhen, 1976 October 14-; Yang, Mi, 1986- ([Publisher not identified], 2017)
"An imperial guard searches for the truth behind a conspiracy that framed him and his parents. The proof of his innocence lies with a wanted woman named Bei Zhai... but will she reveal what she knows? In this intense prequel to Brotherhood of Blades, the only thing he can truly trust is his sword."--Container.